Probing Diversity of Type II Supernovae with the Chinese Space Station Telescope - Lin, Han; Zhang, Jujia; Zhang, Xinghan (Universe (Basel), 2023)
Type II supernovae (SNe II), which show abundant hydrogen in their spectra, belong to a class of SNe with diverse observed properties. It is commonly accepted that SNe II are produced by core collapse and explosion of massive stars. However, the large photometric and spectroscopic diversity of SNe II and the mechanisms responsible for this diversity are not thoroughly understood. In this review, we first briefly introduce the optical characteristics and possible progenitors of each subtype of SNe II. We then highlight the role of the Chinese Space Station Telescope in future SN studies. With a deep limiting magnitude, the main survey project could detect SN IIP-like objects as distant as z∼1.2 and obtain UV-optical follow-up for peculiar transients, especially those long-lived events. With a high resolution and a large field of view, the main survey camera is powerful in linking a nearby SN with its progenitor, while the integral field spectrograph is powerful in revealing the SN environment. All this information has the potential to help enrich our understanding of supernova physics.